Mica paper treating fluid, fireproof mica plate for energy storage battery pack and preparation method of fireproof mica plate

A mica paper treatment liquid with specific components and a controlled preparation process enhances the aging resistance of mica boards, addressing moisture absorption issues and improving performance in energy storage battery packs.

CN119121684AActive Publication Date: 2024-12-13HUNAN RUIDA MICA NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411400541.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-13
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Traditional mica boards used in energy storage battery packs suffer from poor aging resistance due to moisture absorption and environmental sensitivity, which affects their performance and reliability.

Method used

A mica paper treatment liquid comprising specific components like high temperature resistant organic silica gel, chloroprene rubber, diaryl secondary amine, and silane coupling agent, along with a preparation process that includes dipping phlogopite mica paper in the liquid and applying a coating, enhances the mica board's aging resistance.

Benefits of technology

The treated mica boards exhibit strong voltage resistance, bending strength, low water absorption, and excellent aging resistance, improving their performance and durability in energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075155570000051
    Figure BDA0005075155570000051
  • Figure BDA0005075155570000061
    Figure BDA0005075155570000061
  • Figure BDA0005075155570000071
    Figure BDA0005075155570000071
Patent Text Reader

Abstract

The invention relates to the technical field of mica materials, and particularly discloses a mica paper treating fluid, a fireproof mica plate for an energy storage battery pack and a preparation method of the fireproof mica plate. The mica paper treating fluid comprises a treating fluid A and a treating fluid B, the treating fluid A is prepared from the following components in parts by weight: 20 to 30 parts of high-temperature-resistant organic silica gel, 10 to 20 parts of chloroprene rubber, 5 to 15 parts of diaryl secondary amine and 0.10 to 0.32 part of silane coupling agent; the treating fluid B is prepared from the following components in parts by weight: 30 to 40 parts of acrylic resin, 6 to 12 parts of aluminum hydroxide, 8 to 12 parts of titanium dioxide, 4 to 6 parts of hexadecyl trimethyl ammonium bromide and 0.2 to 0.4 part of coupling agent. The invention further discloses a fireproof mica plate prepared from the mica paper treating fluid. The fireproof mica plate prepared by the technical scheme of the invention has the advantages of high voltage resistance, bending strength, low water absorption and excellent aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of mica materials, and in particular to a mica paper treatment liquid, a fireproof mica board for an energy storage battery pack, and a preparation method thereof. Background Art

[0002] At present, the fire-retardant material of the battery pack inside the energy storage power station on the market mainly uses mica board. The traditional mica board is mainly made of silicone resin, which is made by pressing multiple layers of mica paper to achieve the required thickness. Since the performance of mica material is greatly affected by the environment and it is easy to absorb moisture, it cannot meet the environmental use requirements of energy storage power stations and cannot meet the requirements of energy storage power stations aging with the environment. Summary of the invention

[0003] In order to improve the aging resistance of mica paper, the present application provides a mica paper treatment liquid, a fireproof mica board for an energy storage battery pack, and a preparation method thereof.

[0004] In a first aspect, the present application provides a mica paper processing liquid, including a processing liquid A and a processing liquid B; The treatment liquid A comprises the following components in parts by weight: 20-30 parts of high temperature resistant organic silica gel, 10-20 parts of chloroprene rubber, 5-15 parts of diaryl secondary amine, and 0.10-0.32 parts of silane coupling agent; The treatment liquid B comprises the following components in parts by weight: 30-40 parts of acrylic resin, 6-12 parts of aluminum hydroxide, 8-12 parts of titanium dioxide, 4-6 parts of hexadecyltrimethylammonium bromide, and 0.2-0.4 parts of coupling agent.

[0005] Mica has good high temperature resistance and insulation. The high temperature resistant organic silica gel in treatment liquid A has a very flexible main chain, and its intermolecular force is weak, providing suitable viscosity, weak surface tension, small surface energy, and strong film-forming ability, so that the surface structure of the mica board after molding is good, and silica gel and chloroprene rubber have good heat resistance and cold resistance, good chemical stability, high rigidity and toughness, good mechanical strength, and can increase the toughness of the mica system. Diaryl secondary amine has anti-aging effect, and coupling agent provides excellent bonding force. In treatment liquid B, aluminum hydroxide and titanium dioxide can fill the pores between the fine particles of treatment liquid B, and cooperate with other substances in treatment liquid B to increase the viscosity and toughness of the system, and at the same time improve the aging resistance of the mica board.

[0006] Preferably, in the treatment liquid A, the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:1-3; the silane coupling agent is selected from any one or more of vinyl silane coupling agent, aminosilane coupling agent, and methacryloxysilane coupling agent; and the high temperature resistant organic silica gel is selected from one or more of SH-9501, SH-9602, and SH-5202S.

[0007] Preferably, in the treatment liquid B, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, propyltriethoxysilane, mercaptopropyltriethoxysilane, ethylenediaminepropyltriethoxysilane, ethylenediaminepropylmethyldimethoxysilane, vinyltriacetoxysilane or vinyltriethoxysilane.

[0008] Preferably, in the treatment liquid B, the coupling agent is composed of a mixture of γ-methacryloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.1-0.5.

[0009] Preferably, the treatment liquid A is prepared by weighing the corresponding weights of the raw material components respectively, stirring for ≥60 min under the condition of a stirring speed ≥500 rpm to prepare the treatment liquid A.

[0010] During the test of the preparation method of the treatment liquid A, the applicant found that when the stirring speed was lower than 500 rpm, the uniformity was poor; when the stirring time was lower than 60 min, the uniformity was poor. Therefore, the present application controls the parameters within the above range.

[0011] Preferably, the preparation method of the treatment liquid B is: weigh the corresponding weights of the raw material components respectively, put them into a reaction kettle, and stir for ≥30 min at a temperature of 50-70° C. and a stirring speed of ≥80 rpm to prepare the treatment liquid B.

[0012] During the test of the preparation method of treatment liquid B, the applicant found that when the temperature of the reactor was lower than 50°C, the film-forming effect was poor; when the temperature of the reactor was higher than 70°C, solidified products appeared in the mixed liquid; when the stirring speed was lower than 80rpm, the mixing was uneven and the coating was uneven; when the stirring time was lower than 30min, the mixing was uneven and the coating was uneven. Therefore, the present application controls the parameters within the above range.

[0013] Furthermore, the temperature of the reactor is 55-65°C.

[0014] During the test of the preparation method of the treatment liquid B, the applicant found that when the temperature of the reactor was 50-55°C or 65-70°C, the water absorption of the prepared fireproof mica board was large, 0.39-0.42%, after the aging test, which reduced the application performance. Therefore, the temperature parameter of the reactor was controlled within the range of 55-65°C in the present application.

[0015] In a second aspect, the present application provides a fireproof mica board for an energy storage battery pack, which is prepared by impregnating phlogopite mica paper with the above-mentioned mica paper treatment liquid.

[0016] In a third aspect, the present application provides a method for preparing the fireproof mica board for the energy storage battery pack, which specifically comprises the following steps: The phlogopite mica paper is dipped in the treatment liquid A through a laminating machine, the laminating machine speed is 5-7 m / min, and the phlogopite mica paper is hot-pressed by a press after laminating to obtain a pre-treated mica board; the parameters of the hot pressing are: hot pressing temperature of 160-200° C., pressure of 1.8-2.2 Mpa, and hot pressing time of ≥20 min; The treatment liquid B is coated on the surface of the pretreated mica board by means of gap coating, the gap of the gap is 0.1±0.02mm, and then the fireproof mica board for the energy storage battery pack is obtained by drying; the drying parameter conditions are: divided into three zones for drying, each zone is 7-9m long, the vehicle speed during drying is 7-10m / min, the temperature of zone 1 is 50-60℃, the temperature of zone 2 is 100-120℃, and the temperature of zone 3 is 130-150℃.

[0017] During the test of the preparation method of the fireproof mica board, the mica board was dipped in the treatment liquid A. The applicant found that: when the speed of the glue machine was lower than 5m / s, the amount of glue (treatment liquid A) was high and bubbles appeared during hot pressing; when the speed of the glue machine was higher than 7m / s, the amount of glue (treatment liquid A) was low and stratification occurred after hot pressing. When the hot pressing temperature was greater than 200°C, the mica board lost powder; when the hot pressing temperature was lower than 160°C, the adhesion between the mica layers was poor. When the pressure was higher than 2.2Mpa, the mica board deformed; when the pressure was lower than 1.8Mpa, the adhesion between the mica layers was poor. When the hot pressing time was lower than 20min, the adhesion between the mica layers was poor.

[0018] During the test of the preparation method of the fireproof mica board, the applicant found that when the mica board was coated with the treatment liquid B, the coating could not be cured when the vehicle speed was lower than 5m / min, and bubbles appeared on the coating surface when the vehicle speed was higher than 7m / min. When the temperature of the first drying zone was lower than 50°C, the solvent in the glue could not be dried in the first zone, and bubbles appeared on the surface when the temperature of the first zone was higher than 60°C; when the temperature of the second zone was lower than 100°C, the coating liquid could not be cured, and bubbles appeared on the surface when the temperature of the second zone was higher than 120°C; when the temperature of the third zone was lower than 130°C, the surface was anti-sticky, and when the temperature of the third zone was higher than 150°C, cracks appeared.

[0019] Preferably, the hot pressing parameters are as follows: hot pressing temperature is 170-190° C., pressure is 1.9-2.1 MPa, and hot pressing time is ≥20 min.

[0020] During the test of the method for preparing the fireproof mica board, the mica board was dipped in the treatment liquid A, and the applicant found that when the hot pressing temperature was 160-170°C or 190-200°C, the water absorption of the mica board after the aging test was large. When the pressure was 1.8-1.9Mpa or 2.1-2.2Mpa, the water absorption of the mica board after the aging test was large. Therefore, the present application controls the hot pressing temperature and pressure parameters within the above range.

[0021] Preferably, the drying parameters are as follows: divided into three zones for drying, each zone being 7.5-8.5 m long, the vehicle speed being 8-9 m / min during drying, the temperature of zone one being 53-58°C, the temperature of zone two being 105-115°C, and the temperature of zone three being 135-145°C.

[0022] During the test of the preparation method of the fire-resistant mica board, when the mica board was coated with the treatment liquid B, the applicant found that when the length of each zone was controlled to be 7.5-8.5m, the vehicle speed during drying was 8-9m / min, the temperature of zone one was 53-58°C, the temperature of zone two was 105-115°C, and the temperature of zone three was 135-145°C, the water absorption of the mica board after the aging test was small, that is, the temperature of each drying zone was controlled within the above range in the present application, which further improved the aging resistance of the mica board.

[0023] In summary, the technical solution of this application has the following effects: The present application uses specific weight portions of high temperature resistant organic silicone, chloroprene rubber, diaryl secondary amine, and silane coupling agent as raw material components of treatment liquid A, and specific weight portions of acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent as raw material components of treatment liquid B. The phlogopite mica paper is dipped in the above-mentioned treatment liquid A through a laminator, and then a press is used to produce mica boards. Then, an anti-aging coating (treatment liquid B) is coated on the surface of the mica board by a gap coating method, and the coating is prepared by drying. The prepared fire-resistant mica board has strong voltage resistance, bending strength, low water absorption, and excellent aging resistance.

[0024] The method for preparing the fireproof mica board provided in the present application is simple to operate and reduces production costs. By controlling the types and amounts of raw materials and the specific process parameters during the preparation method, the occurrence of bubbles, stratification, pores, embrittlement, cracks, powder loss, unevenness, orange peel and other undesirable phenomena during the forming process of the fireproof mica board is avoided.

[0025] The present application further improves the aging resistance of the fireproof mica board by screening the type of diaryl secondary amine in the treatment liquid A and the type of coupling agent in the treatment liquid B. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a process flow chart of the method for preparing the fireproof mica board for the energy storage battery pack in the embodiment of the present application. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application. Example

[0028] Examples 1-19 Examples 1-19 respectively provide a fireproof mica board for an energy storage battery pack and a preparation method thereof.

[0029] The difference between the above embodiments is that the amounts of the components in the treatment liquid A and the treatment liquid B are different, as shown in Table 1.

[0030] The process flow chart of the preparation method of the fireproof mica board for the energy storage battery pack in the above embodiment is as follows Figure 1 As shown, the specific steps are: The preparation method of treatment liquid A is as follows: according to Table 1, the corresponding weights of the raw material components, namely, high temperature resistant organic silica gel SH-9602, chloroprene rubber, diaryl secondary amine (composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:2), and silane coupling agent (KH-560) are respectively weighed, and stirred for 80 minutes at a stirring speed of 600 rpm to prepare a mica paper treatment liquid.

[0031] The preparation method of treatment liquid B is as follows: according to Table 1, the corresponding weights of the raw material components acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent (composed of a mixture of γ-methacryloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.3) are weighed respectively, put into a reaction kettle, and stirred for 40 minutes at a temperature of 60°C and a stirring speed of 100 rpm to prepare treatment liquid B.

[0032] The phlogopite mica paper (the model of the mica paper is P506, purchased from Pingjiang County Weipai Mica Insulation Material Co., Ltd.) is dipped in the treatment liquid A through a laminator, and the laminator speed is 6m / min. After the phlogopite mica paper is laminated, it is hot-pressed using a press to obtain a pretreated mica board; the hot-pressing parameter conditions are: hot-pressing temperature is 180°C, pressure is 2.0Mpa, and hot-pressing time is 25min.

[0033] The treatment liquid B is coated on the surface of the pretreated mica board by the gap coating method, and then dried to obtain the fireproof mica board for the energy storage battery pack, with a gap of 0.11 mm; the drying parameter conditions are: divided into three zones for drying, each zone is 8 m long, the vehicle speed during drying is 8.5 m / min, the temperature of zone 1 is 55°C, the temperature of zone 2 is 110°C, and the temperature of zone 3 is 140°C.

[0034] Table 1 Amount of each component in the treatment solution A and the treatment solution B in Examples 1-19 Examples 20-23 Examples 20-23 respectively provide a fireproof mica board for an energy storage battery pack and a preparation method thereof.

[0035] The difference between the above embodiment and embodiment 1 is that the type of diaryl secondary amine in the treatment solution A is different, as shown below.

[0036] In Example 20: the diaryl secondary amine is composed of a mixture of N-phenyl-α-naphthylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:2.

[0037] In Example 21: the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 2:9.

[0038] In Example 22: the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:1.

[0039] In Example 23: the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:3.

[0040] The other raw materials and the preparation method of the mica board in the above embodiment are the same as those in embodiment 1.

[0041] Examples 24-27 Examples 24-27 respectively provide a fireproof mica board for an energy storage battery pack and a preparation method thereof.

[0042] The difference between the above embodiment and embodiment 1 is that the type of coupling agent in the treatment liquid B is different, as shown below.

[0043] In Example 24: the coupling agent is composed of a mixture of γ-methacryloxypropyltrimethoxysilane and propyltriethoxysilane in a weight ratio of 1:0.3.

[0044] In Example 25: the coupling agent is composed of a mixture of γ-methacryloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 0.3:1.

[0045] In Example 26: the coupling agent is composed of a mixture of γ-methacryloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.1.

[0046] In Example 27: the coupling agent is composed of a mixture of γ-methacryloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.5.

[0047] The other raw materials and the preparation method of the mica board in the above embodiment are the same as those in embodiment 1.

[0048] Comparative Example Comparative Examples 1-18 Comparative Examples 1-18 respectively provide a mica board and a preparation method thereof.

[0049] The difference between the comparative example and Example 1 is that the amounts of the components in the treatment liquid A and the treatment liquid B are different, as shown in Table 2.

[0050] Table 2 Amount of each component in the treatment solution A and the treatment solution B in Comparative Examples 1-18 The preparation methods of the mica plates in the above comparative example and embodiment 1 are the same.

[0051] Comparative Examples 19-22 Comparative Examples 19-22 respectively provide a mica board and a preparation method thereof.

[0052] The differences between the above comparative example and Example 1 are specifically as follows.

[0053] In Comparative Example 19: an equal amount of methyl vinyl silicone rubber was used to replace chloroprene rubber.

[0054] In Comparative Example 20: an equal amount of polyimide resin was used to replace the acrylic resin.

[0055] In Comparative Example 21: an equal amount of aluminum hydroxide was used to replace titanium dioxide.

[0056] In Comparative Example 22: an equal amount of aluminum silicate was used to replace aluminum hydroxide.

[0057] The other raw materials and the preparation method of the mica board in the above comparative example are the same as those in Example 1.

[0058] Performance testing (1) Surface properties: Observe whether there are defects on the surface of the mica board during the preparation process and on the surface of the prepared mica board product.

[0059] (2) Voltage resistance: With reference to the national standard GB / T5019.2-2009 test method, the voltage resistance performance of the mica board was tested using a voltage resistance tester.

[0060] (3) Bending strength: The bending strength performance of the mica board is tested using a bending strength tester.

[0061] (4) Water absorption rate: Soak the mica board in water for 60 minutes, take out the absorbent paper and gently wipe it dry, and use an electronic balance to test the water absorption rate of the mica board.

[0062] (5) Aging resistance: The mica board was exposed to a double-lamp closed carbon arc for 720 hours to test its voltage resistance, bending strength and water absorption.

[0063] Test results: as shown in Table 3.

[0064] Table 3 Performance test results of mica boards in Examples 1-27 and Comparative Examples 1-22 It was found through experiments that the mica board surface prepared by the technical solution of the present application was intact and free of defects during the preparation process, and after the aging test, the mica board sample was still intact and free of defects.

[0065] When the high temperature resistant organic silica gel in the treatment liquid A in Comparative Example 1 was less than 20 parts by weight, the mica board layers were delaminated (the mica board was formed by laminating multiple layers of mica paper).

[0066] When the high temperature resistant organic silica gel in the treatment liquid A in Comparative Example 2 was higher than 30 parts by weight, bubbles appeared on the surface of the mica board.

[0067] In Comparative Example 3, when the chloroprene rubber in the treatment liquid A was less than 10 parts by weight, the mica board layers delaminated after aging.

[0068] When the chloroprene rubber in the treatment liquid A in Comparative Example 4 was higher than 20 parts by weight, pores appeared between the mica board layers.

[0069] When the content of diaryl secondary amine in the treatment solution A in Comparative Example 5 was less than 5 parts by weight, the mica plate became brittle after aging.

[0070] When the content of diaryl secondary amine in the treatment solution A in Comparative Example 6 was higher than 15 parts by weight, pores appeared between the mica plate layers.

[0071] When the silane coupling agent in the treatment liquid A in Comparative Example 7 was less than 0.10 parts by weight, the mica paper was delaminated after curing.

[0072] In Comparative Example 9, when the acrylic resin in the treatment liquid B was less than 30 parts by weight, the surface film formation was poor.

[0073] When the acrylic resin in the treatment solution B in Comparative Example 10 was higher than 40 parts by weight, cracks appeared on the coating after drying.

[0074] When the aluminum hydroxide in the treatment solution B in Comparative Example 11 was less than 6 parts by weight, the coating cracked after aging.

[0075] When the aluminum hydroxide in the treatment liquid B in Comparative Example 12 was higher than 12 parts by weight, the surface was powdered after drying.

[0076] When the titanium dioxide in the treatment solution B in Comparative Example 13 is less than 8 parts by weight, the weather resistance of the coating surface is poor.

[0077] When the titanium dioxide in the treatment solution B in Comparative Example 14 was higher than 12 parts by weight, the coating surface was uneven and had an orange peel appearance.

[0078] When the content of hexadecyltrimethylammonium bromide in the treatment solution B in Comparative Example 15 was less than 4 parts by weight, the coating lost its gloss after aging.

[0079] When the content of hexadecyltrimethylammonium bromide in the treatment solution B in Comparative Example 16 was higher than 6 parts by weight, white powder appeared on the coating surface.

[0080] When the coupling agent in the treatment liquid B in Comparative Example 17 was less than 0.2 parts by weight, the coating fell off.

[0081] When the coupling agent in the treatment liquid B in Comparative Example 18 was higher than 0.4 parts by weight, a solidified product appeared in the mixed liquid.

[0082] Combined with Table 2, by comparing the test results of Examples 1-27 with Comparative Examples 8 and 19-24, it can be seen that the present application uses high temperature resistant organic silica gel, chloroprene rubber, diaryl secondary amine, and silane coupling agent as raw material components of treatment liquid A, and uses acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent as raw material components of treatment liquid B. The phlogopite mica paper is dipped in the above-mentioned treatment liquid A through a laminator, and then a press is used to produce mica boards, and then an anti-aging coating (treatment liquid B) is coated on the surface of the mica board by a gap coating method. The coating is prepared by drying, and the prepared fire-resistant mica board has strong voltage resistance, bending strength, low water absorption, and excellent aging resistance.

[0083] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A mica paper treatment liquid, characterized in that: including a treatment liquid A and a treatment liquid B; The treatment liquid A comprises the following components in parts by weight: 20-30 parts of high temperature resistant organic silica gel, 10-20 parts of chloroprene rubber, 5-15 parts of diaryl secondary amine, and 0.10-0.32 parts of silane coupling agent; The treatment liquid B comprises the following components in parts by weight: 30-40 parts of acrylic resin, 6-12 parts of aluminum hydroxide, 8-12 parts of titanium dioxide, 4-6 parts of hexadecyltrimethylammonium bromide, and 0.2-0.4 parts of coupling agent.

2. The mica paper treating liquid according to claim 1, characterized in that: In the treatment liquid A, the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:1-3; the silane coupling agent is selected from any one or more of vinyl silane coupling agent, aminosilane coupling agent, and methacryloxysilane coupling agent; and the high temperature resistant organic silica gel is selected from one or more of SH-9501, SH-9602, and SH-5202S.

3. The mica paper treating liquid according to claim 1, characterized in that: In the treatment liquid B, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, propyltriethoxysilane, mercaptopropyltriethoxysilane, ethylenediaminepropyltriethoxysilane, ethylenediaminepropylmethyldimethoxysilane, vinyltriacetoxysilane or vinyltriethoxysilane.

4. The mica paper treating liquid according to claim 1, characterized in that: In the treatment liquid B, the coupling agent is composed of a mixture of γ-methacryloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.1-0.

5.

5. The mica paper treating liquid according to claim 1, characterized in that: The preparation method of the treatment liquid A is as follows: weigh the corresponding weights of the raw material components respectively, stir for ≥60 min under the condition of a stirring speed ≥500 rpm, and prepare the treatment liquid A.

6. The mica paper treating liquid according to claim 1, characterized in that: The preparation method of the treatment liquid B is as follows: weigh the corresponding weights of the raw material components respectively, put them into a reaction kettle, and stir for ≥30 minutes at a temperature of 50-70° C. and a stirring speed of ≥80 rpm to prepare the treatment liquid B.

7. A fireproof mica board for energy storage battery pack, characterized in that: The phlogopite paper is prepared by subjecting the phlogopite paper to a gum-impregnation treatment using the mica paper treatment solution described in any one of claims 1 to 6.

8. The method for preparing the fireproof mica board for the energy storage battery pack according to claim 7, characterized in that: The specific steps include: The phlogopite mica paper is dipped in the treatment liquid A through a laminating machine, the laminating machine speed is 5-7 m / min, and the phlogopite mica paper is hot-pressed using a press after laminating to obtain a pre-treated mica board; The parameters of the hot pressing are: hot pressing temperature of 160-200°C, pressure of 1.8-2.2Mpa, and hot pressing time of ≥20min; The treatment liquid B is coated on the surface of the pretreated mica board by means of gap coating, the gap of the gap is 0.1±0.02mm, and then the fireproof mica board for the energy storage battery pack is obtained by drying; the drying parameter conditions are: divided into three zones for drying, each zone is 7-9m long, the vehicle speed during drying is 7-10m / min, the temperature of zone 1 is 50-60℃, the temperature of zone 2 is 100-120℃, and the temperature of zone 3 is 130-150℃.

9. The method for preparing the fireproof mica board for the energy storage battery pack according to claim 8, characterized in that: The parameters of the hot pressing are as follows: the hot pressing temperature is 170-190° C., the pressure is 1.9-2.1 MPa, and the hot pressing time is ≥20 min.

10. The method for preparing the fireproof mica board for energy storage battery pack according to claim 8, characterized in that: The drying parameters are as follows: divided into three zones for drying, each zone being 7.5-8.5 m long, the vehicle speed being 8-9 m / min, the temperature of zone 1 being 53-58° C., the temperature of zone 2 being 105-115° C., and the temperature of zone 3 being 135-145° C.

Citation Information

Patent Citations

  • High-strength and high-heat-insulation fiber composite fireproof mica plate

    CN116330769A

  • New energy automobile waterproof mica plate and preparation method thereof

    CN117153504A